The Correlation Between Uric Acid Levels (Photometer Method) And The Incidence of Hypertension in Prolanis Patients at Puskesmas Klirong II Kebumen Regency - Budi Setyawan; Retno Sulistiyowati; Umi Solikhah (Institute of Computer Science (IOCS), 2022)
Health service through Prolanis (Program Pengelolaan Penyakit Kronis or Chronic Disease Management Program in English) is a management program for health maintenance in order to achieve an optimal quality of life. One of the targets of prolanis is patients with hypertension. Hypertension can cause the blockage of uric acid crystals in blood vessels so that kidney function is disrupted. As a result, there is an increase in uric acid levels. Based on a preliminary study conducted on March 14, 2022, at Puskesmas Klirong II, it was found that 23 prolanis patients had complaints of joint pain, while 38 of them had hypertension. This research aimed to find out whether there is a correlation between uric acid levels and the incidence of hypertension in prolanis patients at Puskesmas Klirong II. The population was 50 people with a sample of 37 people. The sample was obtained by employing random sampling. This was an Analytical Observational research with a Cross-Sectional research design. The uric acid levels were checked with the Urikase-PAP photometer method. This research was conducted in May 2022. The results showed that 4 respondents had normal uric acid levels and normal blood pressure. On the other hand, there were 12 respondents who had normal uric acid levels and high blood pressure. Meanwhile, the other 21 respondents had high uric acid levels and high blood pressure. The results of the Fisher's Exact Test statistical test obtained a p-value = 0.028 <0.05. It was concluded that there was a correlation between uric acid levels (photometer method) and the incidence of hypertension in prolanis patients at Puskesmas Klirong II, Kabupaten Kebumen.